Mediações docentes em fóruns educacionais do curso de letras da Universidade Federal do Pará - Lobato, Maria Cristina Ataide (2012)
This study was motivated by the demands of knowledge about the relationships of teaching and learning in interactive virtual spaces, in search of more adequate strategies and to promote, among students, the construction of knowledge. The research is an exemplar of Applied Linguistics and it focuses on teacher mediation in virtual education forums of the Federal University of Pará Letters Course Specialization in Portuguese with the purpose of advancing knowledge about challenges of teaching in distance education. The investigative work was developed in the light of Vygotsky (1934/2007, 1934/2008) socio-cultural-historical conception of the human development, particularly the concepts of mediation, and with the theoretical support of the research model developed by Garrison and Anderson (2003), in particular those pertaining to social presence and teaching presence. The theoretical tools for analyzing the teachers lexicogrammatical choices in the forum are the concepts of Systemic Functional Linguistics, particularly those relating to interpersonal metafunction. The study showed that the forums are privileged spaces for interactions between teachers and students in distance courses and that the learning, in these environments, can be motivated and directed by teachers interventions, with a particular focus on the motivation of learning, encouraging interaction and promotion of community practices. The results suggest that the appropriate action planning and teacher training for mediation in virtual forums are predictive of better results in student learning